Spatial Concentration and Spillover: Eviction Dynamics in Neighborhoods of Los Angeles, California, 2005–2015. Issue 3 (3rd September 2021) - Nelson, Kyle; Gromis, Ashley; Kuai, Yiwen; Lens, Michael C.
ABSTRACT: The lack of sufficient affordable housing in Los Angeles, California burdens many renter households with the threat of an eviction. Research has identified individual- and neighborhood-level sociodemographic correlates of eviction, but the uneven distribution of sociodemographic characteristics and housing conditions across neighborhoods likely produces broader patterns of spatial clustering in eviction prevalence across local areas. We use spatial autoregressive models to explain the spatial concentration and spillover effects for two types of formal eviction filings—court-based and no-fault Ellis Act petitions—within and across census tracts in Los Angeles. Court-based filings show greater and more persistent spatial concentration, particularly in neighborhoods with higher percentages of Black residents. We find evidence of spatial correlation for both types of eviction, however, suggesting that identifying the spatial distribution of eviction prevalence across local areas is important to understanding how location shapes eviction risk in metropolitan areas.